Ethnomathematical analysis of student activities in associating quadrilateral and triangle concepts - Amaliyah, Yika; Marsigit, Marsigit (Universitas Papua, 2024)
Through integrating local culture into learning, students can observe the application of mathematical concepts in real-life contexts. Therefore, this research aims to outline the steps involved in incorporating ethnomathematics of Yogyakarta batik motifs into the teaching of quadrilateral and triangle concepts in mathematics at private junior high schools in Sleman Regency, Yogyakarta. A qualitative case study approach was employed, involving eight seventh-grade students selected through purposive sampling based on specific criteria. Data were collected via observations, document analysis, and interviews. The findings indicated that the implementation of ethnomathematics-based activities using Yogyakarta batik motifs was successful. Students demonstrated positive responses and enthusiasm. The instructional steps for these association activities included: introducing students to Yogyakarta ethnomathematics, presenting examples of batik motifs, explaining the cultural values embedded in these motifs, identifying rectangular and triangular patterns within the motifs, engaging students in creating simple batik designs that incorporate these geometric elements, and discussing and sharing their work.